The Interrelationship of Fraud Triangle Saving Plan Case - Purba, Rosalia Jasmine Alicia; Rusydi, Mohamad Khoiru (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2023)
PT Asuransi Jiwasraya is the oldest life insurance company in Indonesia. PT. Asuransi Jiwasraya has constantly undergone changes and development to meet the needs and capabilities of the communities. This study aims to determine how the interrelationship between the three factors in the Fraud Triangle became the impetus for the suspects to commit fraud in the Saving Plan case of PT Asuransi Jiwasraya (Persero) in 2018. This qualitative research implemented interviews with four professionals who are Forensic Accountants from Accounting Firms and a Mid-Associate from a Law Firm. The findings revealed that perpetrators used three factors in the Fraud Triangle, which are Pressure, Opportunity and Rationalization, to do unethical behaviors. Weak internal control and the poor quality of Good Corporate Governance increased the opportunity factor, the pressure factor that came from the burden of showing a good financial report to satisfy shareholders, and the rationalization of perpetrators that consider those acts normal. Ultimately, The Audit Board of the Republic of Indonesia has succeeded in uncovering the fraud committed by the perpetrators. Abstrak PT Asuransi Jiwasraya merupakan perusahaan asuransi jiwa tertua di Indonesia. PT Asuransi Jiwasraya terus mengalami perubahaan dan perkembangan untuk memenuhi kebutuhan dan kemampuan masyarakat. Penelitian ini bertujuan untuk mengetahui bagaimana keterkaitan ketiga faktor dalam segitiga fraud atau Fraud Triangle menjadi pendorong bagi para tersangka untuk melakukan tindak kecurangan dalam kasus Saving Plan PT Asuransi Jiwasraya (Persero) tahun 2018. Penelitian kualitatif ini dibuat dengan melakukan wawancara kepada empat orang profesional yang merupakan tiga Akuntan Forensik dari salah satu Big Four dan Mid-Associate dari firma hukum. Temuan mengungkapkan bahwa pelaku menggunakan ketiga faktor dalam segitiga kecurangan yaitu Tekanan, Peluang dan Rasionalisasi untuk melakukan tindakan tidak etis. Lemahnya pengendalian internal dan buruknya Good Corporate Governance perusahaan menjadi faktor meningkatnya Peluang. Faktor tekanan berasal dari beban keharusan untuk menampilakn laporan keuangan yang baik demi memuaskan pihak ketiga serta rasionalisasi para pelaku yang menganggap tindakan tersebut normal. Badan Pemeriksa Keuangan Republik Indonesia akhirnya berhasil mengungkap kecurangan yang dilakukan oleh para pelaku.